2016
DOI: 10.1128/jvi.01239-16
|View full text |Cite
|
Sign up to set email alerts
|

An Ebola Virus-Like Particle-Based Reporter System Enables Evaluation of Antiviral Drugs In Vivo under Non-Biosafety Level 4 Conditions

Abstract: Ebola virus (EBOV) is a highly contagious lethal pathogen. As a biosafety level 4 (BSL-4) agent, however, EBOV is restricted to costly BSL-4 laboratories for experimentation, thus significantly impeding the evaluation of EBOV vaccines and drugs. Here, we report an EBOV-like particle (EBOVLP)-based luciferase reporter system that enables the evaluation of anti-EBOV agents in vitro and in vivo outside BSL-4 facilities. Cotransfection of HEK293T cells with four plasmids encoding the proteins VP40, NP, and GP of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Disparities in previous antibody-mediated neutralization results could be due to differing experimental conditions and model systems (Davidson et al, 2015; Li et al, 2016; Wilkinson et al, 2017; Wilson et al, 2000). Thus, we characterized the neutralization of each mAb in three assays: i) replication-competent vesicular stomatitis virus bearing EBOV GP (rVSV); ii) biologically contained EBOV (ΔVP30) (Halfmann et al, 2008); and iii) authentic EBOV (Figure 2) performed under BSL-2+, BSL-3 and BSL-4 containment, respectively, as previously described, to ensure consistency with previous studies.…”
Section: Resultsmentioning
confidence: 98%
“…Disparities in previous antibody-mediated neutralization results could be due to differing experimental conditions and model systems (Davidson et al, 2015; Li et al, 2016; Wilkinson et al, 2017; Wilson et al, 2000). Thus, we characterized the neutralization of each mAb in three assays: i) replication-competent vesicular stomatitis virus bearing EBOV GP (rVSV); ii) biologically contained EBOV (ΔVP30) (Halfmann et al, 2008); and iii) authentic EBOV (Figure 2) performed under BSL-2+, BSL-3 and BSL-4 containment, respectively, as previously described, to ensure consistency with previous studies.…”
Section: Resultsmentioning
confidence: 98%
“…We reasoned against chemically synthesized RNA as a template because blood nucleases rapidly degrade such biomaterials at ambient temperatures, 20 which could prove problematic with minimal assay formulations. On the other hand, de novo construction of in vitro produced, non-infectious, and/or replication-deficient EBOV virions, 21 an approach common for many well-studied species of mammalian viruses, was actively discouraged outside high containment for reasons of health, safety, and biosecurity. We thus elected to use commercially available recombinant MS2 coliphage as our primary surrogate template (AR14), despite the robustness of this virion compared to the easily fragmentable nature of filovirus particles, 22 and pseudotyped lentivirus (PV) based on HIV manufactured in-house as a fallback template (see ESI, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some pseudoviral-particle neutralization assays based on the luciferase reporter system have been reported that allow the evaluation of anti-EBOV agents in laboratories with a lower biosafety level of containment (BSL-2)1920. The EBOV glycoprotein (GP) is solely responsible for viral attachment to, fusion with, and entry into new host cells, and it is therefore a major target of vaccine and drug design efforts2122.…”
mentioning
confidence: 99%